Modern American literature - Cerrito, Joann; DiMauro, Laurie (Gale virtual reference library, 1999)
Provides insight into the careers of nearly 500 20th-century American writers, including black and women writers. Entries include important critical excerpts, chronologically arranged and collected from a wide variety of sources such as books, scholarly journals, general periodicals and newspapers.